Ustalanie kosztów relewantnych na potrzeby decyzji operacyjnych przy wykorzystaniu planowania scenariuszowego - Nadolna, Bożena (Establishing of Relevant Cost for Operation Decisions with the Use of Scenario Planning, 2007)
The process of making a decision in the conditions of big variability of an enterprise is especially difficult. A person who takes it should have precise information of all factors which characterize decision variants in the range of operation decisions. This information can be delivered by the scenario plans. They enable to determine the information which is essential for decisions that is income and relevant costs which individual decision options differentiate from. The aim of the article is to present the role of the scenario plans in establishing of relevant costs for operation decisions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 386-394